2023
DOI: 10.3389/fsurg.2023.1097927
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of early gastric cancer with different level of undifferentiated component and nomogram to predict lymph node metastasis

Abstract: BackgroundFew studies showed that mixed type early gastric cancer (EGC) relates to higher risk of lymph node metastasis. We aimed to explore the clinicopathological feature of GC according to different proportions of undifferentiated components (PUC) and develop a nomogram to predict status of lymph node metastasis (LNM) in EGC lesions.MethodsClinicopathological data of the 4,375 patients who underwent surgically resection for gastric cancer in our center were retrospectively evaluated and finally 626 cases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It has been suggested that ulcerative findings, a depressed appearance, diffuse type, and undifferentiated lesions are risk factors for LNM in EGC [5,8,13,17,22]. Depressed types tend to have higher rates of LNM in T1b cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that ulcerative findings, a depressed appearance, diffuse type, and undifferentiated lesions are risk factors for LNM in EGC [5,8,13,17,22]. Depressed types tend to have higher rates of LNM in T1b cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been substantial research on the prediction of risk factors for LNMs in EGC, no definitive criteria are available [15]. Risk factors for LNM are well established in Eastern countries [5,16,17]. Nevertheless, an analysis of predictive factors for LNMs in EGC remains uncommon in the West, where series of patients are smaller in comparison to the East [3,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation